Modernization of control system of the beam critical parameters at a LU-10 industrial electron accelerator - Pomatsalyuk, R.I.; Uvarov, V.L.; Shevchenko, V.A.; Shlyakhov, I.N. (Вопросы атомной науки и техники, 2017)
Continuous control and monitoring of critical parameters of radiation processing of products is one of the requirements of the international standard ISO 11137. The current system to monitoring the parameters of radiation treatment of products at the LU-10 accelerator is being in operation for more than 15 years. The life-time of the mayor part of measuring modules is over, and those modules are no longer produced. Modernization of monitoring system with the use of the multi-functional USB modules, single-board mini-computers and EPICS control system (Experimental Physics and Industrial Control System) is considered. The architecture and software for a new monitoring system have been developed. Debugging and operation of the system in a test mode is performed.